Asumsi Terhadap Manusia Sebagai Suatu Organisasi Dalam Pengembangan Organisasi Di SDN 05 Situjuah Gadang Di Kecamatan Situjuah Limo Nagari - Lenny Ristiani (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to understand how the assumption of humans as an organization is applied in the process of organizational development at SDN 05 Situjuah Gadang. The research employed a descriptive qualitative approach through observation, interviews, and documentation study. The findings reveal that humans within the school organization function as mini- organizational systems possessing interconnected structures, functions, and goals. The principal, teachers, staff, and students interact through mechanisms of communication, collaboration, and continuous adaptation. Organizational development in the school is proven not to occur instantly but through participatory and reflective processes involving all human elements within it. By perceiving humans as dynamic and complex organizations, the school can create a collaborative, adaptive, and quality-oriented working environment that supports continuous improvement in educational outcomes.